On the exponential growth of some multidimensional stable densities - Kalinauskaitė, N. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Н. Б. Калинаускайте. О показательном убывании некоторых мноомерных устойчивых плотностейN. Kalinauskaitė. Daugiamačių stabilių tankių eksponentinio gesimo klausimu